The effect of parental pain, disability benefits and education on risk of long-term sick leave due to musculoskeletal disorders and the modifying effect of sleep and physical activity: the HUNT study - Karoline Moe; Eivind Schjelderup Skarpsno; Tom Ivar Lund Nilsen; Paul Jarle Mork; Lene Aasdahl (BMC, 2024)
Abstract Background Family factors, sleep, and physical activity have previously been associated with risk of sick leave and disability benefits due to musculoskeletal disorders. However, how these factors act during adolescence and young adulthood is unclear. The aim of this study was to (i) examine if chronic pain, disability benefits and education in parents influence the risk of long-term sick leave due to musculoskeletal disorders in young adulthood, and (ii) to explore if offspring sleep problems and physical activity modify these effects. Methods A population-based prospective study of 18,552 adolescents and young adults (≤ 30 years) in the Norwegian HUNT Study. Survey data was linked to national registry data on sick leave, disability benefits, family relations and educational attainment. We used Cox regression to estimate hazard ratio (HR) with 95% confidence interval (CI) for long-term (≥ 31 days) sick leave due to a musculoskeletal disorder in offspring associated with parental factors and the joint effect of parental factors and offspring lifestyle factors. Results Parental chronic pain (HR 1.36, 95% CI 1.27-1.45), disability benefits (HR 1.41, 95% CI 1.33-1.48) and low educational attainment (HR 1.78, 95% CI 1.67-1.90) increased the risk of long-term sick leave due to musculoskeletal disorders among offspring. There was no strong evidence that sleep and physical activity modified these effects. Conclusion Chronic pain, disability benefit and low education in parents increased the risk of long-term sick leave due to musculoskeletal disorders among offspring, but these effects were not modified by offspring sleep problems or physical activity level. The findings suggest that efforts beyond individual lifestyle factors might be important as preventive measures.